Overall survival in advanced hepatocellular carcinoma treated with concomitant systemic therapy and stereotactic body radiation therapy or systemic therapy alone - Piening, Alexander; Swaminath, Anand; Dombrowski, John; Teague, Ryan M.; Al-Hammadi, Noor; Shahi, Jeevin (Frontiers in Oncology, 2023)
Introduction First-line systemic therapy (ST) options for advanced hepatocellular carcinoma (HCC) include tyrosine kinase inhibitors and immunotherapy (IO). Evolving data suggest prolonged overall survival (OS) when ST is combined with stereotactic body radiation therapy (SBRT), although evidence is significantly limited in HCC populations. We hypothesized that advanced HCC patients in the National Cancer Database (NCDB) would have improved OS when receiving ST+SBRT vs ST alone. Methods Stage III/IV HCC patients diagnosed from 2010-2020 and treated with first-line ST±SBRT were identified from the NCDB. The primary endpoint was OS from date of diagnosis stratified by the receipt of SBRT (ST+SBRT vs ST alone). Survival was estimated using Kaplan-Meier methodology and compared via log-rank. Multivariate analysis (MVA) was performed by Cox regression. Results Of 10,505 eligible patients with stage III disease, 115 (1.1%) received ST+SBRT and 10,390 (98.9%) received ST alone. Of 9,617 eligible patients with stage IV disease, 127 (1.3%) received ST+SBRT and 9,490 (98.7%) received ST alone. Median follow-up time was 6.8 months. Baseline characteristics were similar between cohorts. Patients with stage III disease receiving ST+SBRT had improved median OS (12.62 months vs 8.38 months) and higher rates of survival at 1-year (53.0% vs 38.7%) and 2-years (27.0% vs 20.7%) compared to those receiving ST alone (log-rank P=0.0054). Similarly, patients with stage IV disease receiving ST+SBRT had improved median OS (11.79 months vs 5.72 months) and higher rates of survival at 1-year (49.6% vs 26.2%) and 2-years (23.6% vs 12.0%) (log-rank P<0.0001). On MVA, receipt of SBRT predicted improved OS (HR=0.748, 95%CI 0.588-0.951; P=0.0178) and receipt of IO trended towards improved OS (HR=0.859, 95%CI 0.735-1.003; P=0.0538). Conclusion In advanced HCC, patients receiving ST+SBRT had improved OS compared to those receiving ST alone. Prospective clinical trials are warranted to better identify HCC populations which may benefit from combined modality therapy.